PENGARUH PENDIDIKAN, PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PRODUKTIVITAS DAN KINERJA UMKM DI KELURAHAN SESETAN DENPASAR SELATAN - Suhartanti, Ni Luh Septiani Vera; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
A good performance of busineess needed to develop because busineess performance will increase the level of productivity and income. The purpose of this study are 1) to analyze education, and the use of information technology directly to productivity at busineess in the Sesetan, 2) to analyze education, use of information technology, and productivity directly to the performance of busineess in the Sesetan, 3) to analyze education , and the use of information technology through productivity towards the performance of busineess in Sesetan. Sample used 111 busineess. Analysis technique used is path analysis. The results showed that 1) Education directly had a positive (not significant) effect on the productivity of busineess in Sesetan. Busineess use modern information technology have higher productivity than busineess traditional information technology. 2) Education directly has a positive (not significant) effect, but productivity has a positive (significant) effect on the performance of busineess in Sesetan. Busineess use modern information technology don’t have higher level performance than busineess utilize traditional information technology. 3) Productivity is not an intervening variable the indirect effect of education and the use of information technology on the performance of MSMEs in Sesetan Kelurahan. Keywords: Education, Utilization of Information Technology, Productivity, Busineess Performance